PEMILIHAN POLA ASUH DAN KEPEMIMPINAN PEMILIK PANTI ASUHAN - Muhammad Qosim (Conciencia, 2019)
This research based on the violence and exploitation cases of orphanage children’s. An orphanage that expected can be solution to resolve orphan and waif problems, but in fact some orphanages in Indonesia generally and especially in Palembang, violence and exploitation cases still happening in the orphanage. In this study case in three orphanages with different background. This research purpose is to analyze parenting system applied at Darul Hijrah, Ar-rohim, and Fitrah orphanage Palembang. The research method is qualitative method, with data collection technique through observation, interview and documentation. And data analysis techniques through the phase of data reduction, data presentation and conclusion drawing. The results of research at three orphanages show that the orphanage owner must choose the right parenting system and the wrong selection parenting can’t separated from the role of the orphanage owner. In this research as exemplified by the Ar-Rohim orphanage which has a democratic parenting applied to orphanage children and the result have a positive impact on the development of orphanage children, both developmental psychology, social development and in terms of intelligence. So the hopes that the orphanage children do not feel lost love and attention from parents can be fulfilled.